2009
DOI: 10.1248/bpb.32.1527
|View full text |Cite
|
Sign up to set email alerts
|

Dual Anti-oxidative Effects of Fraxetin Isolated from Fraxinus rhinchophylla

Abstract: Atherosclerosis is main cause of arteriosclerosis. The pivotal role of low-density lipoprotein (LDL) oxidation in atherogenesis suggests antioxidants may help prevent cardiovascular disease. Fraxinus rhynchophylla DENCE (Oleaceae) is a traditional medicinal plant from East Asia. During the course of characterizing potential drug candidates from natural products, we isolated two major coumarins, esculetin and fraxetin and found that fraxetin has dual-antioxidative functions. Low concentrations (1-5 m mM) of fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…However, we found that nuclear translocation of p65, the active subunit of NF-kB, was not altered by 30 mM trans-resveratrol (30 mM is the most active concentration for the induction of HO-1 by trans-resveratrol in rat VSMCs). Because transfection efficiency in rat VSMC is extremely low, NF-kB-dependent reporter activity was performed using MEF cells [28]. NF-kB reporter activity was not significantly changed in MEF cells treated with 3-30 mM trans-resveratrol (Fig.…”
Section: Nrf2/are Activation Is Required For Ho-1 Induction By Trans-mentioning
confidence: 99%
“…However, we found that nuclear translocation of p65, the active subunit of NF-kB, was not altered by 30 mM trans-resveratrol (30 mM is the most active concentration for the induction of HO-1 by trans-resveratrol in rat VSMCs). Because transfection efficiency in rat VSMC is extremely low, NF-kB-dependent reporter activity was performed using MEF cells [28]. NF-kB reporter activity was not significantly changed in MEF cells treated with 3-30 mM trans-resveratrol (Fig.…”
Section: Nrf2/are Activation Is Required For Ho-1 Induction By Trans-mentioning
confidence: 99%
“…The compound fraxetin was also identified in a related species Jatropha podagrica 19 . Fraxetin was also detected in Fraxinus rhinchophylla, Cortex fraxini and Lawsonia inermis and are proven as antioxidants [20][21][22] . Fraxetin is an antihyperglecemic compound, which prevents rotenone-induced apoptosis by induction of endogenous glutathione in human neuroblastoma cells 23 .…”
Section: Fig3: Antioxidant Activity Of Different Solvent Extracts Ofmentioning
confidence: 98%
“…Aesculin, a 6, 7-dihydroxycoumarin-6-O-D-β-glucopyranoside, is a coumarin glucoside naturally found in stem barks of Fraxinus rhynchophyllycosidea and widely used for the treatment of diarrhea, leukorrhea, and inflammatory diseases such as arthritis and gout [14,18,19]. The anti-inflammatory activity of aesculin is attributed to activating nuclear factor-E2-related factor 2 (Nrf2) as well as inhibiting NF-κB [5,15].…”
Section: Introductionmentioning
confidence: 99%